1997
DOI: 10.1088/0953-2048/10/11/007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hole filling by La and hole doping by Ca on the superconductivity of

Abstract: The structural and superconducting properties of ( samples have been studied by x-ray diffraction, resistivity, a.c. susceptibility and oxygen content measurements. The effect of increasing La concentration in is in lowering the carrier concentration and decreasing , which is attributed to hole filling by La. This suppression of has been compensated by appropriate hole doping with Ca in (, which shows that for a fixed La content increases dramatically as the Ca content increases. For instance, in the oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 21 publications
6
15
0
Order By: Relevance
“…On the other hand, Ca 2+ substitution at RE 3+ site causes recovery of T c in underdoped RE123 samples [1,2]. Similar works have also been reported for other RE123 systems [3][4][5][6][7]. Similar works have also been reported for other RE123 systems [3][4][5][6][7].…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…On the other hand, Ca 2+ substitution at RE 3+ site causes recovery of T c in underdoped RE123 samples [1,2]. Similar works have also been reported for other RE123 systems [3][4][5][6][7]. Similar works have also been reported for other RE123 systems [3][4][5][6][7].…”
Section: Introductionsupporting
confidence: 77%
“…Substitutions of trivalent RE 3+ at the Ba site have been reported to lower critical temperature, T c with increasing RE 3+ concentration [1,2]. Interestingly, a combination of both Ca 2+ substitution at Nd 3+ site and La 3+ at Ba 2+ site showed hole filling by La 3+ was completely balanced by hole doping due to the Ca 2+ substitution [1,3]. Interestingly, a combination of both Ca 2+ substitution at Nd 3+ site and La 3+ at Ba 2+ site showed hole filling by La 3+ was completely balanced by hole doping due to the Ca 2+ substitution [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…Four Nd-doped samples (y = 0.1 to 0.4) displayed nearly tetragonal structure, whereas all the five Ca-Nd doped samples (x = 0.1, 0.2, 0.3 and y = 0.3; x = 0.2, 0.4 and y = 0.4) remain orthorhombic with distortion (b − a)/(b + a) very close to that of pure NdBCO. The refined unit cell parameters for Er(Ba 2−y La y )Cu 3 O z are reported elsewhere [19], exhibiting orthorhombic structure for y = 0.0 to 0.3 and tetragonal structure for y = 0.4. It is interesting to note that the Nd-doped NdBCO samples undergo suddenly an orthorhombic to tetragonal transition at y > 0.1 whereas the La-doped ErBCO [19] and YBCO [10,13] samples display the same orthorhombic to tetragonal transition at y = 0.4.…”
Section: Resultsmentioning
confidence: 99%
“…The refined unit cell parameters for Er(Ba 2−y La y )Cu 3 O z are reported elsewhere [19], exhibiting orthorhombic structure for y = 0.0 to 0.3 and tetragonal structure for y = 0.4. It is interesting to note that the Nd-doped NdBCO samples undergo suddenly an orthorhombic to tetragonal transition at y > 0.1 whereas the La-doped ErBCO [19] and YBCO [10,13] samples display the same orthorhombic to tetragonal transition at y = 0.4. This indicates that the magnetic character of Nd suppresses orthorhombic structure much faster than the non-magnetic La substitution for Ba in RBCO.…”
Section: Resultsmentioning
confidence: 99%
“…Essentially, by varying the type and amount of dopant, different properties could be expected, which offers exciting possibilities to prepare material with desired properties. Several re- ports showed that doping causes a prominent effect towards structural, electrical, and magnetic properties of the superconductor [6,7], and [8]. Researchers found that valence of dopant plays an important role in determining the effective copper valence where the T c is influenced [9].…”
Section: Introductionmentioning
confidence: 99%